Effect of discrete deposition and segregated heat-treatment on the macro- and microstructure, and tensile properties of large-scale titanium alloy components by laser melting deposition. (October 2021) - Xie, Yong; Zhou, Qingjun; Yan, Zhenyu; Feng, Chen; Cong, Baoqiang; Wang, Guoqing; Wang, Fude
Abstract: The challenge of fabrication large-scale laser melting deposited titanium alloy (LLMDT) components was high residual stress, warpage deformation, and even fracture during long-time continuous deposition. To address this challenge, a method named discrete deposition and segregated heat-treatment (DDSH) was used to fabricate the LLMDT components and its effect on the macro- and microstructure, and tensile properties have been systematically studied. The results showed the macrostructure of the DDSH interface region showed columnar grains due to its higher thermal gradient and lower solidification rate than them in other LLMDT parts with columnar grains and equiaxed grains. The microstructure in the whole LLMDT components consisted of ultrafine basket-weave microstructure. The average width of the α lamellae in the DDSH interface region and other LLMDT parts was 0.38–0.424 μm and 0.477–0.54 μm, respectively. The average width of α lamellae was finer in the DDSH interface region than that in the other LLMDT parts owing to its higher thermal gradient and higher cooling rate compared with the other LLMDT parts. For the LLMDT components in different directions with the same region, the UTS and the YS in the H-sample were slightly higher than those in the V-sample, while the EL in the H-sample was lower than those in the V-sample. The anisotropic ductility was owing to the continuous grain boundary exhibited different fracture mechanisms under different directions with loading stress. For the LLMD components in different regions with the same direction, the highest fluctuation ratio of the UTS, the highest fluctuation ratio of the YS, and the highest fluctuation ratio of the EL was 0.012%, 0.08%, and 0.145%, respectively. The reason was the average with of the α lamellae in the whole LLMDT components showed a little difference.